2018
DOI: 10.1080/16506073.2018.1513554
|View full text |Cite
|
Sign up to set email alerts
|

Mediation analyses of Internet-facilitated cognitive behavioral intervention for maternal depression

Abstract: This study evaluated the putative mediating mechanisms of an Internet-facilitated cognitivebehavioral therapy (CBT) intervention for depression tailored to economically disadvantaged mothers of preschool-age children. The CBT mediators were tested across two previously published randomized controlled trials which included the same measures of behavioral activation, negative thinking, and savoring of positive events. Trial 1 included 70 mothers with elevated depressive symptoms who were randomized to either the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Finally, a total of 26 RCTs met the eligibility criteria and were included in this review. Half of these studies examined samples with clinically depressed patients (n = 2769) (Choi et al, 2014;Clarke et al, 2014;Forand et al, 2018;Hirsch et al, 2018;Lamers et al, 2015;Newby, Williams, & Andrews, 2014;Pictet, Jermann, & Ceschi, 2016;Pots, Trompetter, Schreurs, & Bohlmeijer, 2016;Seeley et al, 2019;Terides et al, 2017;van der Zanden, Galindo-Garre, Curie, Kramer, & Cuijpers, 2014;Warmerdam, van Straten, Jongsma, Twisk, & Cuijpers, 2010;Williams, Blackwell, Mackenzie, Holmes, & Andrews, 2013); whereas the other 13 studies focused on samples in which depression symptoms were assessed without applying a clinical cut-off score (i.e., "non-clinical"), comprising mixed samples with other physical and mental impairments, or without pathology (n = 4051) (Auyeung & Mo, 2018;Bakker, Kazantzis, Rickwood, & Rickard, 2018;Heckendorf, Lehr, Ebert, & Freund, 2019;Kauer et al, 2012;Levin, Haeger, Pierce, & Twohig, 2017;Ma, She, Siu, Zeng, & Liu, 2018;Morgan, Mackinnon, & Jorm, 2013;Morris, Schueller, & Picard, 2015;Querstret, Cropley, & Fife-Schaw, 2018;van Luenen, Kraaij, Spinhoven, Wilderjans, & Garnefski, 2019;Viskovich & Pakenham, 2018;Viskovich & Pakenham, 2019;Willems et al, 2017). Table 1 provides a detailed overview on study characteristics and extracted data.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, a total of 26 RCTs met the eligibility criteria and were included in this review. Half of these studies examined samples with clinically depressed patients (n = 2769) (Choi et al, 2014;Clarke et al, 2014;Forand et al, 2018;Hirsch et al, 2018;Lamers et al, 2015;Newby, Williams, & Andrews, 2014;Pictet, Jermann, & Ceschi, 2016;Pots, Trompetter, Schreurs, & Bohlmeijer, 2016;Seeley et al, 2019;Terides et al, 2017;van der Zanden, Galindo-Garre, Curie, Kramer, & Cuijpers, 2014;Warmerdam, van Straten, Jongsma, Twisk, & Cuijpers, 2010;Williams, Blackwell, Mackenzie, Holmes, & Andrews, 2013); whereas the other 13 studies focused on samples in which depression symptoms were assessed without applying a clinical cut-off score (i.e., "non-clinical"), comprising mixed samples with other physical and mental impairments, or without pathology (n = 4051) (Auyeung & Mo, 2018;Bakker, Kazantzis, Rickwood, & Rickard, 2018;Heckendorf, Lehr, Ebert, & Freund, 2019;Kauer et al, 2012;Levin, Haeger, Pierce, & Twohig, 2017;Ma, She, Siu, Zeng, & Liu, 2018;Morgan, Mackinnon, & Jorm, 2013;Morris, Schueller, & Picard, 2015;Querstret, Cropley, & Fife-Schaw, 2018;van Luenen, Kraaij, Spinhoven, Wilderjans, & Garnefski, 2019;Viskovich & Pakenham, 2018;Viskovich & Pakenham, 2019;Willems et al, 2017). Table 1 provides a detailed overview on study characteristics and extracted data.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…* In these studies the mediator and/or the outcome instruments were deployed on more than two assessment points (including follow-up), but the actual evaluation on temporality (i.e., the mediator changed before the outcome) was not conducted or reported. a When evaluating this criterion, the sample sizes of both trials in the study of Seeley et al (2019) were pooled.…”
Section: Cognitive Mediatorsmentioning
confidence: 99%
“…However, it is less clear whether behavioral activation also works as a mechanism of change through which CBT achieves its effects (for example by increasing responsiveness to reward; Forbes, 2020) or whether the behavioral procedures in CBT mostly induce changes in dysfunctional thinking that are responsible for the subsequent changes in depression (Lorenzo-Luaces, Keefe, & DeRubeis, 2015). Findings of studies that tested behavioral activation as a potential mediator in CBT are mixed (Seeley et al, 2019;Takagaki et al, 2016). Specific mechanisms in IPT have been investigated less extensively (Lipsitz & Markowitz, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, considering a broader understanding of ER, several studies can be identified. Two explored the mediational role of repetitive negative thinking (Lamers et al, 2015;Newby et al, 2014), one study analyzed worry and problem orientation (Warmerdam et al, 2010), one psychological flexibility (Pots et al, 2016), and also two behavioral activation (Forand et al, 2018;Seeley et al, 2019). This last study of Seeley and colleagues also explored the mediational role of savoring.…”
Section: Er As a Mechanism Of Change In Internet Interventionsmentioning
confidence: 99%